VALIDITAS DAN PRAKTIKALITAS E-MODUL TITRASI ASAM BASA BERBASIS PENDEKATAN SAINTIFIK UNTUK KELAS XI SMA/ MA - Sari, Reno Pelita (journal of residu, 2019)
This study aims to produce  e-module acid base titration based scientific approach and reveal the level of validity and practicality of the e-module. The type of research used is development research or Research and Development (R & D) using the Plomp development model (Preliminary Research, Prototyping Stage, and Assessment Phase). The research instrument used in the form of questionnaires in the form of validity sheets and practicality of- e-acid base titration module-based scientific approach validated by 5 validators consisting of 2 chemistry lecturers from FMIPA UNP,1  lecturer graphic design/multimedia FT UNP and 2 chemistry teachers from SMAN 15  Padang. Practicality tests were carried out on 2 chemistry teachers and 20 students of class XII of SMAN 15 Padang. The results of the analysis of the validity sheet, the practicality of the teacher and the practicality of the students showed the average moment scores of kappa (k) were 0.83, 0.84 and 0.88, respectively. The data obtained shows that the e-module acid base titration based scientific approach - is valid and practical. Keywords: e-module, Acid-Base Titration, Scientific Approach,, plomp model